Migraine, menopause and hormone replacement therapy. Issue 1 (March 2018) - MacGregor, E Anne
Perimenopause marks a period of increased migraine prevalence in women and many women also report troublesome vasomotor symptoms. Migraine is affected by fluctuating estrogen levels with evidence to support estrogen 'withdrawal' as a trigger of menstrual attacks of migraine without aura, while high estrogen levels can trigger migraine aura. Maintaining a stable estrogen environment with estrogen replacement can benefit estrogen-withdrawal migraine particularly in women who would also benefit from relief of vasomotor symptoms. In contrast to contraceptive doses of ethinylestradiol, migraine aura does not contraindicate use of physiological doses of natural estrogen. In women with migraine with or without aura, using only the lowest doses of transdermal estrogen necessary to control vasomotor symptoms minimizes the risk of unwanted side effects. Cyclical progestogens can have an adverse effect on migraine so continuous progestogens, as provided by the levonorgestrel intrauterine system or in continuous combined transdermal preparation, are preferred. There are no data on the effect of micronized progesterone on migraine, either cyclical or continuous. Non-hormonal options for both conditions are limited but there is evidence of efficacy for escitalopram and venflaxine.